Ab Initio Calculations of Chitosan Effects on the Electronic Properties of Unpassivated Triangular ZnO Nanowires Oriented along [0001] Directions - Thirumuruganandham, Saravana Prakash (2022)
In recent years, both chitosan and ZnO nanostructures have been identified as potential antibacterial substances; however, the potential applications of chitosan adsorbed on ZnO nanowires have not been explored and could offer exciting new perspectives for both materials, for example, in biocompatible electronic circuits. In this work, we investigate the effect of chitosan on the electronic properties of triangular ZnO nanowires (ZnO NWs) from a theoretical perspective. All calculations were performed using density functional theory within the generalized gradient approximation. We considered six different positions of the chitosan molecule (CS) on the nanowire surface. We varied the amine position of CS, viewing it parallel, perpendicular, and at a 45° angle with respect to the NW axis. Our results show that all configurations are chemically stable; moreover, the interaction of the NW surface with the OH radical of CS creates flat states within the band gap energy of the ZnO NWs that might resemble p-doping. In addition, these states induce changes in the band gap energy of the ZnO NWs. All NWs show high chemical stability regardless of the CS position; hence, the adsorption results of all NW assemblies appear to be chemically favorable.